The Effect of Mangosteen Peel (Garcinia mangostana L) Extract Against Mice (Mus musculus) Kidney Cell Damage Induced by Paracetamol - Namira Qisthina; Bambang Widjokongko; Sigit Setyawan (Nexus Kedokteran Translasional, 2014)
Background: Mangosteen peel (Garcinia mangostana L) contains antioxidant such as xanthone core, ?-mangostin, ?-mangostin, ?- mangostin, and garcinone which is thought to be nefroprotector. This study is aimed to investigate the mangosteen peel (Garcinia mangostana L) extracts nefroprotector effect against mice (Mus musculus) kidney cell damage induced by Paracetamol. Methods: This is an experimental laboratory study with post test only controlled group design. Swiss Webster mice weighing around 20 g were selected as sample. Those mice were divided into 4 groups randomly, each group consist of 7 mice. Incidential sampling was used as a sampling technique. Mice in control group (KK) and first treatment group (KP1) were given aquades, while second treatment group (KP2) and third treatment group (KP3) were given 10 mg and 15 mg of mangosteen peel extract respectively. KP1, KP2, and KP3 were given 0.1 ml paracetamol on the 8th, 9th, and 10th day of the treatment. Mice were sacrificed on 4th day and the kidneys were made into preparate using paraffin block and HE staining method. Histological kidney cells were assesed by the sum of pyknosis, karyorrhexis, and karyolysis cells. Data were analyzed using One Way ANOVA test continued by Post Hoc Multiple Comparisons (LSD). Result: One-Way ANOVAs test result showed a significant differences between four groups. LSDs test result showed a significant differences between KK-KP1, KK-KP2, KK-KP3,KP1- KP2, KP1- KP3, KP2-KP3. Conclusion: Mangosteen peel extract can prevent mices kidney cell damage induced by parasetamol. Keywords: Mangosteen peel extract, parasetamol, mices kidney cell damage